KLASIFIKASI PELANGGAN PRODUK INDIHOME MENGGUNAKAN NAIVE BAYES CLASSIFIER DENGAN SELEKSI FITUR ALGORITMA GENETIK - Indah Purnama Sari (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
Classification is a method of data mining used to organize data systematically or according to some rules or rules that have been established. PT. TELKOM as a state-owned company engaged in telecommunications and its development has a variety of telecommunications products that need to be marketed. Marketing strategies are intended to market the company's products for profit especially when it comes to offering new products. However, too many inappropriate offers to customers will only make marketing inefficient and effective. To simplify the marketing strategy of PT. TELKOM then made the classification of telephone subscribers and speedy that already exist in PT. TELKOM Jakarta which has the potential to become a new product customer of Indihome so that the marketing done by PT. TELKOM becomes more effective and efficient. This research uses data mining classification with Naive Bayes Classifier with genetic algorithm as feature selection . This is because Naive Bayes Classifier tends to perform well and can learn quickly in various classification problems, as evidenced by the results of classification accuracy in this study included in the category of good classification.